Qualificação de Instrumentos para Análise da Política de Inclusão Escolar na Ótica de Professores - Moraes, Maiara Cristina (Universidade Federal de São Carlos, 2023)
The National School Inclusion Policy from the Perspective of Inclusive Education guarantees the teaching of the target audience of Special Education (PAEE) in common class schools and its execution in conjunction with other legal provisions and plans proposed in the country have been the subject of studies nationals indicating their limits and challenges. The process of monitoring the school inclusion policy is an urgent topic that requires mechanisms that can actually raise indicators about the context of practice experienced. In this sense, a research agenda has been carried out in order to contribute to large-scale measurement tools, of which the present study is part. Thus, this work aims to verify the perspective of teachers of common education and specialized educational services regarding the school inclusion policy experienced and contribute to the analysis of the relevance and quality of the instrument proposed for this analysis. The research has a descriptive and qualitative approach, and included the participation of the Special Education manager of a municipality in the interior of São Paulo, a teacher, seven teachers working in common education with experience with PAEE students in their classes, and eight Education teachers Special. An interview was carried out with the manager to characterize how the network was organized regarding assistance to PAEE students. With the other participants, the School Inclusion Policy Assessment Questionnaire instruments were applied in the format of individual interviews: Common Education Teacher (QUAPOIE-PC) – version 5, and the School Inclusion Policy Assessment Questionnaire: Special Education Teacher (QUAPOIE-PE) – version 5. The interviews were recorded and transcribed and analyzed, compiling the responses per question. The results indicate that the school inclusion policy has been applied and interpreted, based on the participants' speeches, still with limitations and challenges regarding collaboration between Special Education teachers and regular education teachers. Another point observed was related to the PAEE student learning process. The participants demonstrated satisfaction with the execution of their work and pointed out that the municipality provided sufficient support, and that specialized educational assistance was a priority service offered by the network. However, they felt that the work carried out in Special Education was little recognized and that they felt lonely, as not everyone knew the role of the AEE teacher. It is considered that the methodological strategies applied allowed achieving the objectives and identifying demands for adapting the instruments with a view to their application as a closed instrument in future studies and also contributing to a brief assessment of the policy of the municipality studied from the perspective of these actors.
Qualification of Instruments for Analysis of School Inclusion Policy from the Perspective of Teachers
Keywords: Educação Especial; Política de Inclusão; Qualificação de Instrumento; Special Education.; Inclusion Policy; Instrument Qualification; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL